Aktivitas Ekstrak Buah Takokak (Solanum torvum) terhadap Mortalitas Cacing Gelang Dewasa - MARTHA VINDA CANDRA; JONATHAN LOODY LUKAS; LOLA ADRIANI; HEBERT ADRIANTO (Universitas Hang Tuah, 2019)
ABSTRACT Background: The most common causes of worm infection in the community is the Soil Transmitted Helminth (STH), one of them is roundworm Ascaris lumbricoides. Indonesia has many medicinal plants that can be utilized because these plants are easy to obtain, the price is affordable and safe from various kinds of side effects compared to synthethic drugs, one of which is turkeyberry (Solanum torvum). The purpose of this study is to find out whether turkeyberry (Solanum torvum) fruit extract have an anthelmintic effect on Ascaris suum worm and what concentration can caused mortality to Ascaris suum worm. Method: This study using five concentrations etanol extract turkeyberry fruits 300 ppm, 600 ppm, 900 ppm, 1200 ppm, 1500 ppm and positive control, namely albendazole. Worm death observed in several hours, 6 hours, 24 hours, 45 hours and 48 hours. The data then analyzed using descriptive and probit analysis. Result: The result of the study show that mortality of the adult worms increases with the increase in the concentration of the extract. LC90 and LC99 of the extract are 747,589 ppm and 1002,313 ppm within 48 hours. The increase in extract concentration also cause the darkening of the Ascaris suum worm’s body. Conclusion: ethanol extract of S. torvum fruit have an anthelmintic effect on Ascaris suum worms in vitro.